Vapor – Liquid Equilibrium of Linalool + β- Caryophyllene and α-Pinene + Linalool at Pressures of 30 and 60 kPa - Faris, Satya Naufal; Fakhira, Amira; Wiguno, Annas; Tetrisyanda, Rizky; Kuswandi, Kuswandi (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2025)
This research aims to obtain equilibrium data from essential oils, namely lavender oil. Lavender flowers are composed of several ingredients, such as essential oils (1-3%), alpha-pinene (0.22%), camphene (0.06%), beta-myrcene (5.33%), cymene (0.30%), limonene (1.06%). %), cineol (0.51%), linalool (26.12%), borneol (1.21%), terpinine-4-ol (4.64%), linalyl acetate (26.32%), geranyl acetate (2.14%), and caryophyllene (7.55%). This research focuses on determining vapor-liquid equilibrium (VLE) data for the binary systems Linalool + β-Caryophyllene and α-Pinene + Linalool at vacuum pressure of 30 kPa and 60 kPa. Research was conducted to support the equilibrium data for distillation process in the essential oil industry, by exploring the characteristics of VLE which is an important parameter in distillation column design. Experiments used a modified Othmer type ebulliometer and composition measurements were carried out using Gas Chromatography-Mass Spectrometry (GC-MS). The equilibrium data were correlated using Wilson, NRTL, and UNIQUAC model equations. The thermodynamic consistency tests have been performed using Wisniak Method. The research results showed that the VLE values obtained are thermodynamically consistent and the model used can correlate equilibrium with satisfactory accuracy. It was obtained from experimental data that for the Linalool + β-Caryophyllene system had the largest Average Absolute Deviation in temperature (AAD T) value of 0.74% and for the Alpha Pinene + Linalool system had the largest AAD T with a value of 0.28% for both pressures.